Blood Donation Fear, Perceived Rewards, Self-Efficacy, and Intention to Return Among Whole Blood Donors in China: A Social Cognitive Perspective - Li, Zhong; Lei, Shuge; Li, Xiaoming; Zhao, Yilun; Dai, Yudong; Jin, Shengxuan; Fu, Qiang; Cai, Xubing; Lin, Zhenping; Tu, Xiaoming (Frontiers in Psychology, 2021)
With the increasing demand from aging population and seasonal blood shortage, recruiting and retaining blood donors has become an urgent issue for the blood collection centers in China. This study aims to understand intention to donate again from a social cognitive perspective among whole blood donors in China through investigating the association between the blood donation fear, perceived rewards, self-efficacy and intention to return. A cross-sectional survey was conducted in six cities, which are geographically and socioeconomically distinct areas in Jiangsu, China. Respondents completed a self-administrated questionnaire interviewed by two well-trained medical students. A total of 191 blood donors were included in the current study. Descriptive analysis, correlation analysis, and a generalized linear regression model were used to explore the association between demographic characteristics, psychological factors, and intention to donate again. After controlling other covariates, donors with higher fear scores reported lower intention to return (P = 0.008). Association between self-efficacy and intention to return was statistically significant (P < 0.001); while the association between intrinsic rewards (P = 0.387), extrinsic rewards (P = 0.939) and intention to return were statistically insignificant. This study found that either intrinsic rewards or extrinsic rewards is not significantly associated with intention to donate again among whole blood donors in China, and fear is negatively associated with intention to donate again. Therefore, purposive strategies could be enacted beyond appeals to rewards and focus on the management of donors’ fear.